The State of the Art in Post-Mortem Redistribution and Stability of New Psychoactive Substances in Fatal Cases: A Review of the Literature - Luis Manuel Menéndez-Quintanal; Jose Manuel Matey; Violeta del Fresno González; Begoña Bravo Serrano; Francisco Javier Hernández-Díaz; Félix Zapata; Gemma Montalvo; Carmen García-Ruiz (Psychoactives)
In post-mortem (PM) investigations, forensic toxicologists attempt to identify legal or illegal substances present before death and determine how they contributed to the cause of death. A critical challenge is ensuring that PM sample concentrations accurately reflect those at the time of death, as postmortem redistribution (PMR) can alter these levels due to anatomical and physiological changes. The PMR phenomenon is called a ‘toxicological nightmare’. PMR significantly affects post-mortem drug concentrations, particularly for lipophilic drugs and those with a high volume of distribution. The emergence of new psychoactive substances (NPSs) has led to a growing recognition of their role as a significant public health concern, frequently associated with fatalities related to polydrug use. These substances are renowned for their ability to induce intoxication at low doses, which has led to the continuous updating of toxicological and forensic methods to improve detection and adopt new analytical standards. The comprehensive detection of NPS metabolites, some of which are still undiscovered, presents an additional analytical challenge, as do their metabolic pathways. This complicates their identification in fatal cases using standard analytical methods, potentially leading to an underestimation of their actual prevalence in toxicological results. Furthermore, the interpretation of analytical results is hindered by the absence of data on PM blood levels and the specific contributions of NPS to causes of death, exacerbated by the lack of knowledge of whether the PMR phenomenon influences them. This paper presents a comprehensive review of the literature on post-mortem cases involving various NPS, categorized according to classifications by the United Nations Office on Drugs and Crime (UNODC) and the European Union Drugs Agency (EUDA). These categories include cathinones, phenylethylamines, arylalkylamines, phencyclidine-type substances, phenmetrazines, piperazines, phenidates, aminoindanes, LSD-like NPSs, tryptamines, fentanyl analogs, designer benzodiazepines, synthetic cannabinoids, and nitazenes. This review covers not only postmortem blood levels but also the stability of the substances studied, the methods of analysis, and attempts to shed some light on the PMR phenomenon. This review used various key terms, such as PMR, NPS, and the names of previously categorized substances and drug analyses across multiple peer-reviewed journals and databases, including Scopus, Google Schoolar, Springer, PubMed, and Wiley Online Library. In addition, references from retrieved articles were examined to identify additional relevant research. Interpreting post-mortem toxicological results is complex and lacks definitive guidelines, requiring a nuanced understanding of its challenges and potential pitfalls. As a result, post-mortem toxicology is often regarded as an art. The primary aim of this review is to provide forensic toxicologists with a comprehensive framework to assist in the evaluation and interpretation of NPS analysis. This guide is intended to complement the existing knowledge and practices applied in forensic laboratories within the toxicological analysis of post-mortem cases.